MONITORING AND EVALUATION OF THE LEVEL OF DEVELOPMENT OF THE EUROPEAN REGIONAL SECURITY COMPLEX - Olena Bulatova; Oleksandr Osaulenko; Olha Zakharova (Baltic Journal of Economic Studies, 2021)
Intensification of destabilizing processes in the world economy, increasing the impact of global challenges and the spread of uncertainty in the conditions of economic activity actualize scientific research to ensure a high level of economic security of countries and regions. This in turn requires a thorough systematic analysis and assessment of the level of security and the state of the security environment based on the development of appropriate methodological tools. Taking it into account, the presented research is aimed at developing a system for monitoring and assessing the level of security development of the countries of the European region, based on the tools of multidimensional assessment and construction of complex integrated indicators. The article is aimed to development of the system for monitoring and assessing the EU security level, which consists of comprehensive assessment of the formation of security development factors, construction of the security level integrated indexes, which allowes to classify the EU countries according to the security level, to identify the features and intensity of the influence of the different determinants on the security level formation, to establish the peculiarities of the EU countries distribution within the regional security space. The object of the study is the regional security complex of the EU, based on the monitoring system – 24 indicators, which are systematized by nature (economic, sociodemographic, environmental) and direction of impact (incentives, disincentives), which are assessed for the period 2010–2019. The results show a high assessment of the integrated level of security in countries such as Ireland, Sweden, Denmark, Austria, Cyprus, Finland, Slovakia, the Netherlands, Luxembourg and Germany; Ireland, the Czech Republic, Hungary, Lithuania, and Denmark have the highest security positions in terms of the economic component of the security level, Cyprus, Slovenia, Ireland, Luxembourg and Slovenia in terms of socio-demographic, and Sweden, Austria, Denmark, Finland and Portugal in terms of environmental security. The reduced impact of the economic security component factors, maintaining a moderate impact of the socio-demographic security component factors, the increasing influence of the environmental factors are determined. Statistical analysis of the distribution of the EU countries by security level in 2010–2019 confirmed the tendency to equalize the level of security development of the EU countries within the regional security complex, to reduce the level of variation of integrated assessments of security levels, to increase the share of countries with high levels. Building a matrix of positioning of the EU countries by the integrated level of security and the intensity of its dynamics allowed to divide the countries and zones of relative security and danger, and to determine that the most risky positions are in Italy, Bulgaria and Romania. The practical significance of the results of the study lies in the possibility of applying the proposed system of monitoring the level of security in the development and implementation of regional security strategy of the EU development, which will more effectively monitor changes, prevent risks and threats, prevent negative consequences.